Uma abordagem do preço de transferência em cooperativa agroindustrial do norte do Paraná - Negri, Juliana Andressa (2008)
The transfer price is a managerial tool with the purpose of coordinating the decisions of a company in the reach of their goals, through a fastened value. It includes the operations of sales or the products transfers, services, being present in decentralized units, in other words, companies that chose for their organizational fragmentation, dividing their fastened structure in areas of businesses. In this context, the main objective of this work was to verify the importance of the transfer pricing used in the decentralized units of a agroindustrial cooperative, studying their procedures, as well as the treatment and identification of the methodology adopted in that inside sale process in the reception divisions and refine of the soy. This way, through a case study, it was tried to identify the participation of the decentralized units in the result of the agroindustrial cooperative of the north of Paraná, and the inside transfer pricing adopted by this organization. Therefore, it is concluded that the performance of each one of the units affects in a direct way the final result of the company, although each responsibility center adopts a pricing mechanism in keeping with their activities. The importance of the administration of the transfer price optimizes this process in a positive way; however it is compacted or very close to the costing ways, harming, consequently, its work as a performance measurer